Pemberdayaan Kelompok Tani Kana Melalui Pelatihan Budidaya Jamur Tiram Berbasis Pemanfaatan Limbah Furniture - Manalu, Adelya Irawan; Pardosi, Lukas; Tobing, Wilda Lumban; Lisnahan, Charles Venirius (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to increase the knowledge and skills of the Kana farmer group in cultivating oyster mushrooms by utilizing furniture waste. The method of implementing this service uses participatory action research with the stages of planning, implementation, monitoring, and evaluation. The evaluation instrument for this activity uses a questionnaire sheet, and then the data obtained is analyzed descriptively. The results of this service show that there is an increase in knowledge about the utilization of furniture waste in oyster mushroom growth media and provide skill experience to farmer groups in cultivating oyster mushrooms.